Effects of consumer characteristics and perceived attributes on perception of fragrances - Cherdchu, Panat (Kansas State University, 2013)
Understanding how consumers perceive fragrances based on different aspects (e.g., hedonic, emotions, term association, expectation of functional benefit, and use occasion, etc.) can help product developers or marketers create the right product or message for consumers. The objective of this study was to understand how consumers from different demographic groups, personality types, and liking patterns responded to fragrance samples. Five masculine odorants were selected and evaluated by 240 consumers across the United States. Results demonstrated that consumers from different groups (classified based on age, gender, or personality) generally differentiated products similarly. However, consumers from different personality segments used the scales differently. That is, persons who were more open, extrovert, or agreeable tended to score higher than the others. Consumers associated the most liked odorants with terms such as clean, crisp, fresh, and natural. In addition, the most liked odorants increased positive emotions, tended to be used across the most occasions, were appropriate for most products, and raised expectations of functional benefits. In contrast, consumers associated the least liked samples with the terms heavy and bold and had negative responses to most items. Similar findings were found when analyses were conducted on consumers classifying based on liking patterns. Each consumer group liked specific odorants; however, the relationship between the most liked samples and the response variables were similar. Analysis results demonstrated that openness to experience was the only personality factor that influenced fragrance acceptance. Consumers from different demographic segments tended to like different fragrances. For example, men tended to like chypré smells, whereas younger consumers tended to like soft floral/powdery scents. One limitation of the study is the number and type of fragrances tested. It is possible that a different set of fragrances could have produced different results. However, the range of fragrances in this study was broad-based and generally covered the types of fragrances typically available in the marketplace.
Keywords: Sensory; Consumer; Fragrance; Perceptions; Behavioral Sciences (0602); Marketing (0338); Personality Psychology (0625)